Pengendali Jendela Geser Menggunakan RemoteDengan Penggerak Motor Dc Brushed - Saputra, Dian, Jatmiko, S.T.M.T (2017)
The ease and practicality of doing something was needed to help the work of man. Man busy with activities indoors, sometimes make people forget the healthy way of life. Therefore, the problems outlined the goal of this research is to design a window that is practical and easy to operate and can facilitate air circulation in the room. This window has a sliding window design has two shutters with one bergdrak window and other windows can not be moved. Mover window using a brushed DC motor 12 volt and window locks use a solenoid door lock 12 V Motor and solenoin connected with three relays that are controlled by the Arduino microcontroller. Two relays are used for propulsion and one relay to solenoid. Receiver RF remote to use to receive signals from the remote and give a signal to the Arduino which already contains the program. Of working voltage of 5 V receiver and got suplly of Arduino. RF Remote has 4 channel consisting of channel A, B, C and D. Channel A serves to open the window to close the window while B, Channel C to unlock while D to lock the window. To stop the motor when the window already has the frame with a pair of 2 microswitch which, when depressed ate the motor can only spin opponent directions. The function of each component can be made to work as desired window.